2006
DOI: 10.1099/jmm.0.46307-0
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus agalactiae Cβ protein gene (bac) sequence types, based on the repeated region of the cell-wall-spanning domain: relationship to virulence and a proposed standardized nomenclature

Abstract: The Cβ protein (Bac) of Streptococcus agalactiae (group B streptococcus; GBS) is an IgA binding protein encoded by bac, of which at least 39 sequence types have been described, based on polymorphisms in the repeated region of the cell-wall-spanning domain (‘bac sequence types’). Cβ is usually found in serotype Ib, less commonly in serotype II, and rarely in other serotypes. The aim of this study was to examine the prevalence, variety and distribution, among GBS serotypes and between invasive and superficial is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
2
6
1
Order By: Relevance
“…Thus, we suggest that β-antigen located on the bacterial surface can interfere with the disease process and play a role of anti-virulent factor (at least, in mice) similarly to hyaluronate lyase of S. pyogenes [41]. It is also in agreement with results of Kong et al who demonstrated that presence of shorter variants of β-antigen is associated with increased virulence [32].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Thus, we suggest that β-antigen located on the bacterial surface can interfere with the disease process and play a role of anti-virulent factor (at least, in mice) similarly to hyaluronate lyase of S. pyogenes [41]. It is also in agreement with results of Kong et al who demonstrated that presence of shorter variants of β-antigen is associated with increased virulence [32].…”
Section: Discussionsupporting
confidence: 92%
“…One of the strains, 168/00, which demonstrated the large diameter of growth inhibition zone, was selected for further study. In this strain, the bac gene has unique allele with the closest similarity with 676a and 676b alleles according to classification of Kong et al [32].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability of rAlp3 antisera to opsonize invasive GBS type III strains bearing the cross-reactive proteins, presumably Rib, is of particular importance given the correlation of low maternal levels of Rib antibody with neonatal GBS disease (28). BCP, encoded by the bac gene, is found on nearly all strains of GBS serotype Ib as well as on some isolates of types Ia, II, and V (31), and approximately 23% of GBS strains contained the bac gene according to bac-specific PCR analysis (21). Our recently developed rBCP ⌬IgA demonstrated a higher degree of efficacy against a BCP-positive GBS type Ia strain when coupled to type III CPS and rAlp3 than as a component of an uncoupled mixture, despite evoking similar levels of maternal IgG.…”
Section: Discussionmentioning
confidence: 99%
“…They were part of a large international collection of GBS isolates which have been studied previously (24,47,48,50). After retesting, many were successfully serotyped and most discrepancies between conventional and molecular serotypes were resolved, but 135 isolates remained nontypeable.…”
mentioning
confidence: 99%